2005
DOI: 10.1152/jn.01013.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saccadic Adaptation on Localization of Visual Targets

Abstract: Objects flashed briefly around the time of a saccadic eye movement are grossly mislocalized by human subjects, so they appear to be compressed toward the endpoint of the saccade. In this study, we investigate spatial localization during saccadic adaptation to examine whether the focus of compression tends toward the intended saccadic target or at the endpoint of the actual (adapted) movement. We report two major results. First, that peri-saccadic focus of the compression did not occur at the site of the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
74
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 36 publications
15
74
2
Order By: Relevance
“…The adaptation involves gain changes in cerebellar and other subcortical structures (Desmurget et al, 1998;Robinson and Fuchs, 2001;Catz et al, 2008;Golla et al, 2008). The adaptation-induced mislocalization suggests effects of adaptation on the cortical level, or at least feedback from cerebellar or subcortical structures onto cortical localization mechanisms (Gaymard et al, 2001;Awater et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adaptation involves gain changes in cerebellar and other subcortical structures (Desmurget et al, 1998;Robinson and Fuchs, 2001;Catz et al, 2008;Golla et al, 2008). The adaptation-induced mislocalization suggests effects of adaptation on the cortical level, or at least feedback from cerebellar or subcortical structures onto cortical localization mechanisms (Gaymard et al, 2001;Awater et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has shown a reciprocal effect between visual localization and saccade targeting: modification of motor parameters by saccade adaptation leads to a distortion of visual localization (Bahcall and Kowler, 1999;Awater et al, 2005;Bruno and Morrone, 2007;Collins et al, 2007). This suggests that visual localization and saccade targeting share a common coordinate system, and common pathways in the brain, such that the signal that codes the required motor parameters to reach an object with a saccade also codes the perceived spatial position of that object.…”
Section: Introductionmentioning
confidence: 99%
“…For example, compression correlates with eye speed such that higher speed results in stronger compression [22]. When visual target information and motor control are put into conflict, such as in anti-saccade [23] or saccadic adaptation [24,25] paradigms, compression occurs towards the motor endpoint.…”
Section: Perceptual and Physiological Phenomena Before And During Sacmentioning
confidence: 99%
“…As it stands, the model explains the above-mentioned effects in a retinocentric frame of reference. To account for effects for which transformations to other coordinate systems may play a role, like the observed compression towards the adapted saccade target position [24] or effects in total darkness [20], the model has to be extended in future studies.…”
Section: Theories and Computational Models Of Peri-and Trans-saccadicmentioning
confidence: 99%
“…Saccade targeting can be adaptively adjusted by artificially displacing the saccade target while the eye moves (McLaughlin, 1967;Hopp and Fuchs, 2004;Pélisson et al, 2010). Oculomotor plasticity is paralleled by changes in visual localization that shift the apparent position of visual objects in space (Bahcall and Kowler, 1999;Awater et al, 2005;Bruno and Morrone, 2007;Collins et al, 2007). Saccadic adaptationinduced distortions of visual space have been found even during fixation, suggesting a common mechanism for saccade and visual targeting (Moidell and Bedell, 1988;Schnier et al, 2010;Zimmermann and Lappe, 2010).…”
Section: Introductionmentioning
confidence: 99%